Предмет: Алгебра,
автор: komieg97lolic
Доведи тотожність 8(х - 3) - (х - 2(х - 3) + 4) = 9(х - 3) - 7. Запиши доведення.
Ответы
Автор ответа:
1
Ответ:
...........
Объяснение:
...........
Приложения:

Автор ответа:
0
Відповідь:
Пояснення:
8(х - 3) - (х - 2(х - 3) + 4) = 9(х - 3) - 7. Перетворюємо ліву частину :
8(х - 3) - (х - 2(х - 3) + 4) = 8(х - 3) - x + 2( x - 3 ) - 4 = 10( x - 3 ) - x - 4 =
= 9( х - 3 ) + 1*( х - 3 ) - x - 4 = 9( х - 3 ) + x - 3 - x - 4 = 9( х - 3 ) - 7.
Отже , дана рівність є тотожністю .
Похожие вопросы
Предмет: Физика,
автор: Timka229454
Предмет: Алгебра,
автор: russvin27
Предмет: Химия,
автор: dara99900
Предмет: Русский язык,
автор: tt9320652
Предмет: История,
автор: d00shirak